Evaluating the Performance of Transjakarta Bus Stops and Road Section Facilities on the Route Pondok Gede-Pulogadung - Widodo Budi; Faza Ahmad Rofid (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Jakarta is one of the metropolitan city is also the capital of Indonesia. Over time, Jakarta's growing in terms of population, BPS is projecting an increase in population of 0.73% of the amount projected in 2018 until 2019 (BPS, 2015). Given this it is necessary also that adequate public transportation to support the mobilization of the daily needs of the residents. One provision of the Public Transport of the Jakarta administration is Transjakarta BRT. This final project aims to determine the load factor, travel time, downtime, waiting time, headways, frequency, circulation time, travel speed, and customer satisfaction on the performance of services that are already on the Transjakarta bus trip Pondok Gede-Pulogadung. The method used is a direct survey on Saturday and Monday from at 6:00 am to 7:00 p.m. WIB.Based results of the analysis already conducted found that, average load factor amounted to 22, 49%, Downtime for 5.9 minutes, headways is 17 minutes, the frequency of vehicle 3.5 vehicles / hour, the average circulation time is over 248 minutes, the average travel speed is over 13km / h. From some of the points mentioned above, the load factor, the time between the frequency of the vehicle, has not been categorized as adequate based on the terms of Minimum Service Standards Transjakarta The time between the average is for 17 minutes, the frequency of vehicle 3.5 vehicles / hour, the average circulation time is over 248 minutes, the average travel speed is over 13km / h. From some of the points mentioned above, the load factor, the time between the frequency of the vehicle, has not been categorized as adequate based on the terms of Minimum Service Standards Transjakarta The time between the average is for 17 minutes, the frequency of vehicle 3.5 vehicles / hour, the average circulation time is over 248 minutes, the average travel speed is over 13km / h. From some of the points mentioned above, the load factor, the time between the frequency of the vehicle, has not been categorized as adequate based on the terms of Minimum Service Standards Transjakarta.